New geopolitical order in Northeast Asia: Japan’s threat perception in post-cold war era / Noor Hilmi Mohd Johan, Mohd Firdauz Mohd Fathir and Nurul Aishah Ab Raman - Mohd Johan, Noor Hilmi; Mohd Fathir, Mohd Firdauz; Ab Raman, Nurul Aishah (Universiti Teknologi MARA, Negeri Sembilan, 2018)
The changing of geopolitical environment in Northeast Asia after the Cold War illustrates some fundamental shift in Japan’s security environment. The post-Cold War era provide a new set of challenges and difficulties that must be diligently comprehend not only by Japanese policy maker but also her military echelon as well. With the receding of Soviet Union threat from the north comes a new and emerging volatile situation from her immediate neighbors; People’s Republic of China and Democratic Republic of Korea. Aside from this, threats from Japan domestic security also did not demonstrate any indication of declination. This article explores each international actor that can be considered as security predicament to Japan and why each actor behaves in an aggressive manner towards Japan. By analyzing issues that occur both domestic and beyond her border, the author show how past threats that emerged will eventually be replace by a new and more volatile situations – instances where PRC challenging Japan sovereignty over Senkaku and DPRK nuclear and ballistic missile test. Variety of methodology tools has been used to provide an adequate data analysis to interpret every states action in Northeast Asia, ranging from the using of primary and secondary sources that seek to contribute to the argument of this article.